Paracoccidioidomycosis: acute-subacute clinical form, juvenile type - Silvio Alencar Marques; Joel Carlos Lastória; Rosangela Maria Pires de Camargo; Mariangela Esther Alencar Marques (Sociedade Brasileira de Dermatologia, 2016)
Abstract: The authors report aspects of paracoccidioidomycosis, acute-subacute clinical form, juvenile type, in a 19-year-old female patient. Paracoccidioidomycosis, juvenile type, classically occurs in young patients, both sexes, with lymphoma-like aspects as initial presentation. However, following the natural history of the disease the lymph nodes assume patterns of infectious disease, as an abscess and fistulae. Systemic dissemination of the disease can occur and lethality and morbidity are significant in this clinical presentation.